The Power of Default on Reddit: A General Model to Measure the Influence of Information Intermediaries. Issue 4 (25th October 2017) - Jürgens, Pascal; Stark, Birgit
Abstract : Information intermediaries like search engines and social networks can represent a source of bias for recipients. Their algorithms, especially concerning filtering, sorting, and personalization, are assumed to skew the representation of news topics and thus create media effects in their own right. Largely as a result of methodological challenges, existing studies have often tested isolated hypotheses without covering the full effects chain from content production to reception by the user. However, the preselection of content performed by intermediaries is only relevant if users choose to rely on it, an assumption that so far lacks broad empirical evidence. Based on a broad review of existing study designs, this article develops a general intermediary effects model. From this model, researchers can derive empirical study designs that capture and differentiate the individual effects of filtering, sorting, and personalization. We then apply the model in an assessment of the news aggregator Reddit's change in capacity to influence its users' information selection. Using counterfactual time series decomposition, we show that changing the sections of the website included in the start page by default can lead to large changes in attention paid to content. These findings substantiate existing assumptions about the power of information intermediaries to shape the information environments of their users.